The Remuneration of British Academics - Rob Euwals; Melanie E. Ward (Institute for the Study of Labor (IZA), 2000)
This paper examines both pay relativities and mechanisms for pay determination within the UK academic labour market drawing upon a particularly detailed data set of 635 academics from five traditional Scottish Universities. In the existing literature, the fact that in many occupations, employees are paid according to explicitly determined wage scales is mostly ignored. We employ salary, grade and spinal point information to incorporate the fixed framework of academic salaries into analysis. Our results outline the importance of individual productivity, measured through publication, grant receipt and teaching skill, in attracting financial reward. We find a large penalty associated with time out of the profession and evidence for the deregulation of established pay and promotion structures. In order to identify those academics most likely to leave the profession, analysis also considers the determinants of individuals? reservation and deserved salary. Controlling for individual characteristics we find that lecturers hold the lowest reservation salaries in relation to their current salary level. The academic profession is therefore most at risk from loosing its staff at this grade. We find however no (self-)selection on the basis of the productivity of individuals.
Keywords: J31; J44; A22; C35; 330; Academic labour market; salary; salary scales; Hochschullehrer; Wissenschaftler; Besoldung; Lohnstruktur; Schätzung; Großbritannien